Mesquite pod (Prosopis spp.) food for goats in the semi-desert - Armijo-Nájera, Martha Gabriela; Moreno Reséndez, Alejandro; Blanco Contreras, Eduardo; Borroel-García, Victoria Jared; Reyes-Carrillo, José Luis (Revista Mexicana de Ciencias Agrícolas, 2019)
The objective of the present study was to evaluate some chemical, energetic and nutraceutical characteristics of the pod of Prosopis spp. in two maturation stages, which was carried out in May and June 2016, in the small property ‘Los Whiles’ located in the municipality of San Pedro de las Colonias, Coahuila, Mexico. The ash content was higher (p> 0.05) in mature pods, while the dry matter, acid detergent fiber, neutral detergent fiber, total nitrogen, crude protein and crude fiber was similar (p> 0.05) between tender and mature pods. The state of maturity of the pods also did not affect (p> 0.05) the energy content, nor the nutraceutical.